Ilio inguinal neurectomy in inguinal hernia - Mohanapriya, T.; Karthikeyan, T. R.; Singh, K. Balaji; Arulappan, T. (International Surgery Journal, 2017)
Background: Inguinal hernia is one of the most common surgery done in any hospital. Chronic inguinal pain is one of the common problem these patients complain of. This study aims at evaluating the long-term outcomes of neuralgia and paraesthesia following routine ilioinguinal nerve division, compared to nerve preservation when performing Lichtenstein’s inguinal hernia repair. Methods: The present study is a randomized controlled trial of 60 cases of inguinal hernias admitted in General Surgery Department in our hospital. The patients were randomly chosen into Lichtenstein hernia repair with ilioinguinal neurectomy or Lichtenstein hernia repair with nerve preservation. After surgery, all patients were monitored carefully for pain and paraesthesia. Pain was assessed using visual analogue scale. Paraesthesia was assessed by the monofilament test and evaluated after comparison with the opposite side. Results: In the present study, the incidence of pain as well as the severity of pain is far higher in the nerve preservation study group as opposed to the neurectomy study group. Hypaesthesia is not a significant complication following ilioinguinal neurectomy and does not significantly add to the morbidity of the patient. Conclusions: Prophylactic neurectomy can be an appropriate solution in the prevention of chronic groin pain following Lichtenstein inguinal hernia repair and can be considered as an ideal inclusion into the standard hernia repair procedures. Hypoesthesia is not a significant complication following ilioinguinal neurectomy and does not significantly add to the morbidity of the patient.